LOAD TRANSFER PLATFORMS - COMPARISON OF DESIGN METHODS (Advances in Civil and Architectural Engineering, 2021)
Constructing embankments on compressible foundation soil normally requires soil improvement measures to reduce the amount and duration of settlement. In the most difficult cases, the soil is improved by using pile foundations. When constructing pile foundations, it is necessary to ensure efficient load transfer from the embankment to the piles, which can be achieved using reinforced soil construction with geosynthetics as reinforcement material. In this paper, we compare the calculations of a bearing capacity of such a platform according to the British and the German standards on the example of a level crossing over a railway line. We describe other calculation methods, critically reviewing the fundamental mechanisms of the reinforcement effects in the calculations.